Change in service capacity against major epidemics before and after COVID-19 epidemic in the Chinese Mainland: a policy document-based analysis - Lan WANG; Peiwu SHI; Qunhong SHEN; Zheng CHEN; Chuan PU; Lingzhong XU; Zhi HU; Anning MA; Zhaohui GONG; Tianqiang XU; Panshi WANG; Hua WANG; et al. (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze the change in service capacity against major epidemics before and after coronavirus disease 2019 (COVID-19) in China for the promotion of the capacity. MethodsVia systematic search on the official websites and the law documents website of Peking University (PKULAW), we collected totally 1 756 policy documents relevant to major epidemic prevention and control issued during 2002 - 2020 by government departments and professional public health institutions in 31 provincial-level administrative divisions of China. Contents about the coverage and assessability of service capacity of major epidemic prevention and control were extracted from the documents and indexes for evaluating national and regional coverage and assessability were calculated based on the extracted contents. Paired signed-rank test was used to analyze changes in the indexes before and during COVID-19 epidemic. ResultsThe coverage of major epidemic prevention and control services has reached 100% in the Chinese mainland in 2019. In comparison to those in 2019 before the emergence of COVID-19 epidemic, the national assessability indexes (%) for service capability of major epidemic prevention and control of pre-, ongoing- and post-stage increased in 2020 by 29.78% (65.59% vs. 50.54%) , 17.54% (72.04% vs. 61.29% ) and 4.34% (38.71% vs. 37.10%). the assessment index for service capability of major epidemic prevention and control of pre-stage increased from 78.79% to 89.39% for eastern region and that of ongoing-stage increased from 65.00% to 76.67% for western region (both P < 0.05); but there was no significant increase in regional assessment index for service capability of major epidemic prevention and control of post-stage. The national assessment index for service capacity of major epidemic prevention and control of whole process increased significantly from 66.00% in 2019 to 73.78% in 2020 after the emergence of COVID-19 epidemic (P < 0.001). ConclusionThe overall service capacity of major epidemic prevention and control has improved after the emergence of COVID-19 epidemic in the Chinese Mainland but the service capacity needs to be improved in central and western regions; in addition, the post-event assessment on the service capacity should be concerned for the promotion of the service capacity.